Integrating Plant Selection, Planting Design, and Landscape Construction for Sustainable Site Development - Ranveer Singh (International Journal of Trends in Horticulture, 2025)
This paper explores the interrelationship between plant selection, planting design, and landscape construction in achieving ecologically sustainable and aesthetically pleasing outdoor environments. Plant selection involves choosing species that are well adapted to site conditions, ecological functions, maintenance regimes, and visual preferences. Planting design refers to the arrangement, composition, and spatial organization of plant materials to meet functional, aesthetic, and environmental objectives. Landscape construction encompasses implementation—from site preparation and planting through establishment, with attention to soil, irrigation, and construction quality. After reviewing relevant literature, types and models of plant selection and planting design are categorized, with examples from campus landscapes, roadside plantings, park cities, and rain gardens. Key criteria that influence plant selection include structural form, climatic adaptation, ecological identity, maintenance effort, economic cost, and visual and sensory qualities. In planting design, principles such as unity, repetition, contrast, scale, texture, colour, seasonal interest, and spatial hierarchy are recurrent. The literature also highlights the importance of site analysis, matching plants to micro‐climates and soil conditions, and designing for low maintenance. Several case studies underscore successful integration: an examination of planting design criteria for visual landscape quality on campuses; roadside plant selection weighted toward structural and ecological criteria; and methods of low maintenance plant landscape construction under the “Park City Concept.” Challenges include balancing aesthetic ambition with maintenance budgets, ensuring plant survival under adverse site conditions, and integrating ecological sustainability into design and construction phases. The paper concludes that a holistic approach—one that begins with careful plant selection based on rigorous site assessment, follows through with thoughtful planting design and high‐quality construction—yields landscapes that are both beautiful and durable. Keywords: plant selection; planting design; landscape construction; sustainable landscapes; ecological adaptation; visual aesthetics.
Keywords: Landscape construction; Plant selection; Planting design; Sustainable landscape; Visual aesthetics